Heat penetration studies of canned cured meat cocktail - Gaballo, Maria Heidi Sibayan; Villarino, Blanca J. (2000)
ABSTRACT Canned meat cocktail is a mixture of cured meat cubes cooked in pineapple-sugar sauce. This study was undertaken to determine the feasibility of canned meat cocktail based on the effects of heat processing on the microbiological stability and organoleptic quality of the finished product. Phase I involved the determination of the most acceptable recipe. Sensory evaluation for the determination of the most acceptable sugar concentration using 15%, 13% and 10% showed that the formulation with the 13% sugar was the most acceptable. Phase II described the heat penetration characteristics of the product. Canned meat cocktail is a low acid food (pH=4.75). The thermal process for canned meat cocktail was derived using the mathematical method (m=5,D_250 =1.6) based on the thermal resistance of CI. sporogenes (PA 3679). The mean total process time needed to achieve commercial sterility of canned meat cocktail is approximately 53 minutes at 240°F in 307x409 cans with F/W 300±10 g. Microbiological analyses yielded positive growth of anaerobic mesophiles and themophiles. There was no observed gas and/ or acid production. Vacuum, percent fill and headspace measurement where within standards. The unattractive color and texture of the product mainly attribute to the harsh heat process and the possibility of microbial spoilage, even with thermal treatment for cured products, negates the feasibility of canned cured meat cocktail at the determined schedule. It is recommended that the production of shelf stable canned meat cocktail be approached using pasteurization temperatures to safeguard organoleptic qualities of the product, notably the color and texture of the meat cubes. Studies on acidification, reducing the water activity of the raw materials and use of sugars such as dextrose should also be investigated.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat, Canned